Systematic Journal Review: Management of Radiofrequency Ablation (RFA) for Thyroid Nodules - Tolkha Amaruddin (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
Benign thyroid nodules are common and may cause compressive symptoms and cosmetic concerns, requiring effective treatment. Radiofrequency ablation (RFA) has emerged as a minimally invasive alternative to surgery; however, variations in technique and outcomes necessitate systematic evaluation. This study synthesizes recent evidence on the effectiveness and safety of RFA for benign thyroid nodules and identifies key technical factors influencing outcomes. A systematic review was conducted following PRISMA guidelines, analyzing studies published between 2020 and 2025 from major scientific databases. Ten eligible articles were included for qualitative synthesis. The results indicate that RFA consistently provides significant short- to mid-term nodule volume reduction, preserves thyroid function, and demonstrates a low complication rate. Most patients achieve optimal outcomes with a single ablation session, and long-term follow-up supports sustained efficacy. Recent international guidelines increasingly endorse RFA as a validated non-surgical treatment, including for large nodules previously managed surgically. The study recommends integrating RFA into national healthcare standards in Indonesia, supported by structured training and competency-based certification, to ensure quality and equitable access. Overall, RFA is confirmed as a safe, effective, and adaptable treatment modality with important implications for clinical practice and health policy.